Pengelompokan Kabupaten/Kota Berdasarkan Indikator Rumah Layak Huni di Provinsi Jawa Barat Tahun 2020 - Ravinsyah Kesuma; Agus Purwoto (Politeknik Statistika STIS, 2022)
Building inclusive, safe, durable, and sustainable cities and housing is the eleventh goal of the Sustainable Development Goals (SDGs). To encourage this goal, indicators of livable houses can be used for evaluation of development programs. The province of West Java is the province with the most population in Indonesia, is not followed by the achievement of good livable housing indicators. The inequality between regencies/cities aggravates this condition. Therefore, it is necessary to have a study to determine an accurate target group to be used as a basis for policymaking. This study aims to grouping regencies/cities based on what aspects are their development priorities. The method used in this study is comparison between hierarchical cluster and k-means cluster analysis. The method that produces the best cluster is a complete linkage dan average linkage method with the smallest standard deviation ratio and succeeded in forming four clusters. The four clusters formed have different characteristics for each indicator of livable houses.